Resistance of Eucalyptus spp. genotypes to eucalyptus brown looper Thyrinteina arnobia (Lepidoptera: Geometridae) - Jesus, Flávio Gonçalves; Nogueira, Luciano; Boiça Junior, Arlindo Leal [UNESP]; Ribeiro, Zulene Antonio [UNESP]; Araújo, Marcio Silva; Zanuncio, José Cola (My University, 2015)
Eucalyptus brown looper Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) is a major lepidopteran defoliator of eucalyptus. The objective of this study was to screen various eucalyptus genotypes and identify sources of resistance to T. arnobia. Leaves of the Corymbia citriodora, Eucalyptus alba, E. brassiana, E. camaldulensis, E. cloeziana, E. dunnii, E. grandis, E. pellita x E. tereticornis, E. resinifera, E. robusta, E. saligna, E. tereticornis, E. torelliana x C. citriodora and E. urophylla genotypes were provided to T. arnobia to assess antibiosis. The duration of the larval and pupal stages (days), pupal weight (mg), pupal and larval viability (%), adult longevity (days), sex ratio and total life cycle (days) were recorded. E. grandis, E. robusta, E. brassiana, E. tereticornis and E. saligna were found to be highly susceptible to T. arnobia, whereas E. torelliana x C. citriodora and E. dunnii showed antibiosis and/or antixenosis. These findings can assist growers in the management of T. arnobia and may be useful in the breeding of eucalyptus resistant to this insect.
Keywords: Defoliator caterpillar; Eucalyptus; Host-plant resistance; Pest management